Experiences of parents with adopted children - Co, Paz Elaine R.; Tamase, Bianca Therese S. (College of Home Economics, University of the Philippines Diliman, 2019)
This is a study on the experiences of Filipino adoptive parents, focusing on their characteristics, their motivations behind adopting, their attitudes toward the perceived stigma on adoptive families, and their unique roles as adoptive parents. . Five adoptive parents or couples coming from different family structures were interviewed and five case studies were developed, narrating their life stories. Transcribed data were used to highlight their experiences through thematic analysis. Results show that the type of adoption the parents underwent had a great impact in their experiences, and their family structure played a role in their motivation to adopt. Aside from showing the legal process of adoption, this study legitimized the existence of informal means of adopting. Moreover, motivations of adoptive parents mainly stemmed from internally-driven reasons such as the desire for a child, infertility, religious duty to fulfill, and companionship. With regard to their attitudes toward the perceived stigma on adoptive families, most of their perception focused on the positive comments they encountered, along with their refusal to acknowledge and internalize negative attitudes. Lastly, data emphasized their unique roles as adoptive parents as responsibilities, which spanned disclosing the details of the adoption, involving the child in the process, supporting the child's search for their biological parents, and deciding to fully love their adopted child. This discussion hopes to inspire the beginning of a more informed discourse on the adoption situation in the Philippines.